Manufacturing engineer's reference book - Koshal, Dalbir (Butterworth-Heinemann, 1993)
Never before have the wide range of disciplines comprising manufacturing engineering been covered in such detail in one volume. Leading experts from all over the world have contributed sections. The coverage represents the most up to date survey of the broad interests of the manufacturing engineer. Extensive reference lists are provided, making this an indispensable work for every engineer in industry. Never before have the wide range of disciplines comprising manufacturing engineering been covered in such detail in one volume. Leading experts from all over the world have contributed sectio.
Keywords: Production engineering -- Handbooks, manuals, etc.; elektronické knihy; electronic books